Salvage of the Failed Total Wrist Arthroplasty: A Systematic Review - Berber, Onur; Gidwani, Sam; Garagnani, Lorenzo; Spiteri, Michelle; Riley, Nicholas; McNab, Ian; Little, Christopher (Journal of Wrist Surgery, 2020)
Background Although the performance of total wrist arthroplasty systems has improved, failure is encountered and is a major challenge to manage.Questions Does physical function improve with surgical management of the failed wrist arthroplasty? Is there an improvement in secondary outcome measures including pain, grip strength, and range of motion? What are the reasons for failure in primary total wrist arthroplasty? What are the complications associated with revision of the failed total wrist arthroplasty? What are the survival profiles of the different revision strategies?Methods A systematic review of available literature was performed. Studies were systematically assessed, and data extracted from suitable studies for review. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) reporting guidelines were adhered to. The study protocol was modified from a previous protocol published on the PROSPERO database.Results Fourteen studies were identified considering 218 patients/214 index operations with a follow-up duration following revision surgery of 2 months to 21 years (silicone wrist arthroplasty—42 cases; nonsilicone wrist arthroplasty—172 cases). The functional outcome of revision surgery was infrequently recorded and documented with only short-term assessments undertaken. Complications were seen in 1:2 revision procedures, with re-revision surgeries required in 21.6% of revised primary nonsilicone arthroplasties. Re-revision rate following a revision arthrodesis was 21.4% (15/70 cases) compared with revision arthroplasty of 34.8% (32/92 cases). Revision arthrodesis nonunion rate was 17.5% (22 cases).Conclusion This review has confirmed the high level of surgical complexity and the likelihood of a complicated postoperative outcome when salvaging a failed wrist replacement.Level of Evidence This is a Level 3, systematic review study.
Keywords: wrist arthroplasty; revision; systematic review